"Ventura County Bracero Camps" Exhibition Poster - Cunningham, Jonathan::::::; Malone, Joel::::::; Cassel, Tristan::::::; Enriquez, Tim::::::; Gorodenzik, Jonathan::::::
Exhibition posters shows a map of the location of Bracero Camps within Ventura County, lists the camps, and lists the companies and corporations employing the Braceros locally. This poster was displayed at the John Spoor Broome Library at California State University Channel Islands in "The Braceros of Ventura County" Exhibition in conjunction with the Smithsonian Institution and the Museum of American History "Bittersweet Harvest: The Bracero Program, 1942-1964" exhibition. The posters reflect the collaborative efforts of Chicana/o Studies, Spanish, History, and Art Capstone programs under the guidance of Luke Matjas, Terry Ballman, Pilar Pacheco and Jose Alamillo.